4x-2=11x-43

Simple and best practice solution for 4x-2=11x-43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-2=11x-43 equation:


Simplifying
4x + -2 = 11x + -43

Reorder the terms:
-2 + 4x = 11x + -43

Reorder the terms:
-2 + 4x = -43 + 11x

Solving
-2 + 4x = -43 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
-2 + 4x + -11x = -43 + 11x + -11x

Combine like terms: 4x + -11x = -7x
-2 + -7x = -43 + 11x + -11x

Combine like terms: 11x + -11x = 0
-2 + -7x = -43 + 0
-2 + -7x = -43

Add '2' to each side of the equation.
-2 + 2 + -7x = -43 + 2

Combine like terms: -2 + 2 = 0
0 + -7x = -43 + 2
-7x = -43 + 2

Combine like terms: -43 + 2 = -41
-7x = -41

Divide each side by '-7'.
x = 5.857142857

Simplifying
x = 5.857142857

See similar equations:

| 49-6x=12x+15 | | 5m(2m-7)=-5 | | -8x-y=-8 | | x^3-8x^2+15x+12=0 | | 2x^2-11x-24=0 | | 2(x+3)-3=8-2x | | -21-9x=-32-9x | | 114-3x=24x+18 | | 8-7x=93-42x | | 7,000,000a=10 | | -8b-10=-7-6b | | -2(7w-5)+4w=2(w+2) | | 48x^2=0 | | -4-5x=8-4x | | 81+5y=-4y | | 2(6t+1)-4(t-1)= | | M^2-13m+26= | | 1/4-1/5= | | 10+9x=98-x | | 7+c=40 | | (c+4)(c-3)+6(1+c^2)=(c-2)(c+2) | | 213-4x=32x+21 | | 1/5(3x+12)=3(1-4x)+12 | | -x+4=5x+22 | | 2k+1=4 | | 6x+14=-51-7 | | c=0.10x+6 | | k(2.2)+k(1.8)+5=15 | | 12x=x/3 | | 6x+10=10x+2+5+1 | | 1/3(x+3)=1/6(2x+6) | | 6x+10=10x |

Equations solver categories